2019
DOI: 10.1126/sciadv.aax6707
|View full text |Cite
|
Sign up to set email alerts
|

A mutually stabilized host-guest pair

Abstract: By using click chemistry, a hexacationic cage was synthesized. The cage contains two triscationic π-electron–deficient trispyridiniumtriazine (TPZ3+) platforms that are bridged in a face-to-face manner by three ethylene-triazole-ethylene linkers. A diversity of π-electron–rich guests can be recognized within the pocket of the cage, driven by host-guest π-π interactions. The cage cavity acts as a protecting group, preventing an anthracene guest from undergoing Diels-Alder reaction. Under ultraviolet (UV) light,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 32 publications
2
9
0
Order By: Relevance
“…The formation of receptor-substrate pairs has been demonstrated 222 to stabilize mutually the individual components. In this system, a covalent organic container, based on the p-electron-deficient building block trispyridiniumtriazine (TPZ 3+ ), was developed using click chemistry.…”
Section: Stabilization Of the Ground States Of Reactive Speciesmentioning
confidence: 99%
“…The formation of receptor-substrate pairs has been demonstrated 222 to stabilize mutually the individual components. In this system, a covalent organic container, based on the p-electron-deficient building block trispyridiniumtriazine (TPZ 3+ ), was developed using click chemistry.…”
Section: Stabilization Of the Ground States Of Reactive Speciesmentioning
confidence: 99%
“…Porous organic cages, an emerging class of porous materials composed of isolated, covalently bonded organic molecules with guest-accessible voids, are useful as host molecules, and have promising applications in selective guest inclusion, gas storage and separation, molecular separations, and nanoscale reaction vessels for catalysis. Since the first pioneering work reported by Cooper et al in 2009, POCs have attracted increasing attention and significant progress has been made in the preparation and use of organic cages with different shapes and sizes to generate new porous organic solids. To date, only a few organic cages with cavity diameters larger than 2 nm have been reported .…”
Section: Introductionmentioning
confidence: 99%
“…It revealed that the “roof” and “floor” of cagearene-2 were planar, which was inherited from the 2,4,6-triphenyl-1,3,5-triazine unit. 16 Unfortunately, it was found that cagearene-2 was not as stable as cagearene-1 which may be due to the instability of the 1,3,5-triazine unit, 17 which obstructed its further use in the research of programmed release.…”
Section: Resultsmentioning
confidence: 99%